1999
DOI: 10.1046/j.1365-2036.1999.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesalazine‐induced apoptosis of colorectal cancer: on the verge of a new chemopreventive era?

Abstract: Background : It is an accepted fact that non‐steroidal anti‐inflammatory drugs (NSAIDs) are potent inhibitors of colorectal carcinogenesis. However, the major disadvantages of NSAIDs are gastrointestinal and renal toxicity. We conducted a prospective pilot study on the effects of the safe salicylic acid derivative, mesalazine, on apoptosis and proliferation of tumour cells and on normal tissue in colorectal cancer patients. Methods : Patients with colorectal cancer were asked to take mesalazine enemas for 14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 29 publications
2
51
2
1
Order By: Relevance
“…Somewhat surprisingly, ASA treatment was also found to augment colonic crypt cell proliferation in positions 3 and 4 in normal mice, with a similar trend observed in DSS-mice. This finding stands in contrast to a previous report that ASA has no effect on human colonic proliferation (Bus et al, 1999), although it must be noted that the distribution of proliferating cells along the crypt axis was not examined in this study. Unexpectedly, no significant increase in proliferation was observed when GLP-2 was given in combination with ASA, although a trend toward an increase was noted.…”
Section: Glp-2 and Therapeutics In Colitis 351contrasting
confidence: 55%
“…Somewhat surprisingly, ASA treatment was also found to augment colonic crypt cell proliferation in positions 3 and 4 in normal mice, with a similar trend observed in DSS-mice. This finding stands in contrast to a previous report that ASA has no effect on human colonic proliferation (Bus et al, 1999), although it must be noted that the distribution of proliferating cells along the crypt axis was not examined in this study. Unexpectedly, no significant increase in proliferation was observed when GLP-2 was given in combination with ASA, although a trend toward an increase was noted.…”
Section: Glp-2 and Therapeutics In Colitis 351contrasting
confidence: 55%
“…Bus et al have demonstrated that 2 wk treatment with 4 g/d mesalazine enema in patient with sporadic CRC resulted in enhanced apoptosis of tumor cells, while no change was seen in the normal mucosa that surrounded the tumor lesion. Moreover, the cellular proliferation rate as assessed by means of Ki-67 expression was unchanged in both the tumor and normal tissue [20] . Studies in rodent models of CRC showed that mesalazine inhibits tumor growth and reduces the number of aberrant cryptic foci [21,22] .…”
Section: Mesalazine Has Direct Inhibitory Effects On Crc Cell Growth mentioning
confidence: 89%
“…Although the exact mechanism of action of mesalazine has still to be elucidated, several potential mechanisms have been suggested, including 5-aminosalicylate-induced inhibition of inflammation by interfering with the metabolism of arachidonic acid, prevention of mucosal generation of leukotrienes and prostaglandins, scavenging of free radicals and mechanisms only recently identified involving inhibition of nuclear factor-kappaB (NFB) and induction of apoptosis (6,18,31,43,47,48,55,57,59) . Additional relevant properties include changes in the production of immune globulins and diminished production of interleukin-1 and partial inhibition of platelet activating factor (PAF) expression, resulting in a decrease in leucocyte trafficking (32) .…”
Section: Discussionmentioning
confidence: 99%